microRNA-23a-5p acts as a potential biomarker for sepsis-induced acute respiratory distress syndrome in early stage - Liu, S; Liu, C; Wang, Z; Huang, J; Zeng, Q (Cellular and Molecular Biology, 2016)
Sepsis is a significant cause of morbidity and mortality worldwide. Acute respiratory distress syndrome (ARDS) is the most common and serious complication of sepsis, which presents with rapid and progressive acute onset respiratory failure. The microRNA-23a-5p, as a kind of circulating microRNA (miRNA), is considered to be a candidate biomarker for cardiovascular diseases. However, correlation between ARDS and miR-23a-5p is also elusive. This study aims to investigate the role of miR-23a-5p as the biomarkers for ARDS. In this study, ARDS was induced by intraperitoneally injected with LPS of Sprague-Dawley rats and serum and lung tissues were collected. The NR8383 macrophages were stimulated with LPS. TNF-Î±, IL-1Î², and miR-23a-5p levels in serum, lung tissues and NR8383 were determined using SYBR-based miRNA quantitative real-time polymerase chain reactions (qRT-PCRs). The results indicated that serum miR-23a-5p was increased by 7 fold, 4 fold and 2 fold at 3 h, 6h, and 12h after injection of LPS, respectively. While the miR-23a-5p in NR8383 was elevated by 3.5 fold, 3 fold, 2.5 fold and 5 fold, at 3 h, 6h, 12h and 24h after stimulated with LPS, respectively. In conclusion, the miR-23a-5p might be employed as the potential biomarkers for ARDS in early stage.